Pengaruh Dana Bagi Hasil, Pertumbuhan Ekonomi, Tingkat Pengangguran, Dan Investasi PMDN, Investasi PMA Terhadap Tingkat Kemiskinan Di Kabupaten Mahakam Ulu - Indira Reisia Angun; Eny Rochaida; Aji Sofyan Effendi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study examines the impact of Revenue Sharing Funds (DBH), economic growth, the open unemployment rate, Domestic Investment (PMDN), and Foreign Investment (PMA) on poverty levels in Mahakam Ulu Regency. The research uses secondary data obtained from the Central Bureau of Statistics (BPS) and related institutions for the 2014–2024 period. The analytical method applied is multiple linear regression using IBM SPSS version 29. The findings show that the independent variables DBH, economic growth, unemployment, PMDN, and PMA do not have a statistically significant effect on poverty levels in the region. Instead, poverty in Mahakam Ulu appears to be shaped more by structural, geographical, and social factors. These include limited accessibility due to regional isolation, inadequate infrastructure, high logistics costs, low human resource quality, and economic dependence on the primary sector. The study concludes that conventional macroeconomic indicators and financial inflows are insufficient to capture the complexities of poverty in Mahakam Ulu. To reduce poverty effectively, strategies should prioritize infrastructure development to overcome geographic barriers, enhance human capital through education and training, and encourage diversification of the local economy beyond extractive industries. Such an integrated approach is expected to create more sustainable poverty alleviation outcomes.